Abdominal Pregnancy: A Case Report - Djakaria, Najmiah; Lotisna, David; Soraya Riu, Deviana (International Journal of Psychosocial Rehabilitation, 2020)
Abdominal pregnancies account for 1.4% of ectopic pregnancies and can often cause massive bleeding, with maternal mortality reaching 6%. A case of abdominal pregnancy occurred in a 32-year-old woman, gravida 1, para 0, with twelve weeks and four days of gestational age, who presented with lower abdominal colic pain. Obstetric ultrasonography revealed an empty uterus and fetal appearance on the extrauterine. The placenta is attached to the anterior region of the bladder, with an estimated fetal age of 12 weeks. Management for this patient was an emergency exploratory laparotomy surgery, right oophorectomy, and adhesiolysis through midline incisions with spinal anesthesia, as well as the administration of methotrexate therapy postoperatively. Intraoperatively, the fetus was located intrabdominal and enveloped by the amniotic membrane; the placenta was attached to the omentum, anterior uterus, and right ovary. The importance of early detection and management of abdominal pregnancy may reduce the risk of bleeding complications and decrease fatality risk.